Talkhang a narrative study on the rhetorical vision of ONESIMO Foundation Incorporated's children in conflict with the law - Rama, Christina Marie C.; Pascual, Grey-An Keith (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2019)
This qualitative study aims to describe the experiences of children in conflict with the law (CICL) who suffered from substance use disorder (SUD) through their narratives. It aims to examin teh foolowing 1) the fantasy theme element present in their narration of their experiences before, during, and after suffering from substance use disorder, 2) the fantasy types with their narratives, (3) their symbolic reality embodied in their rhetorical vision. To address the study's problem and objectives, this study is structured in five chapters: (1) Introduction, a brief overview of the issue tackled by the study and also its problem, objectives, significance and its scope and limitation; (2) Review of related literature, that provides academic basis or background to the elements and topics discussed in this study; (3) Methodology, a discussion on the whole process of acquiring and analyzing data; (4) Findings and Analysis, describing and interpreting the data gathered; lastly (5) Summary and conclusion, a summary of all the interpreted data and its how the interpretations can be reflected to a larger scale. The study is for various reasons but mainly because of its purpose of giving light to the stories behind the children who suffered from substance use disorder. This whole study study speaks for these children. This study provides researches and in-depth discussions on the drug condition in the Philippines, substance use disorder amongst children, narratives, and rhetorical vision. The study applied Ernest's Bormann's Fantasy Theme Analysis and Herbert Blumer's Symbolic Interaction Theory as framework. As one- on -one in-depth interview was conducted to gather data for the study with the children in conflict with the law, who suffered from substance use disorder, under the care of ONESIMO Foundation Incorporated ages fifteen to nineteen (15-19) years old. All the informants suffered from substance use disorder and then later on developed delinquent behaviors. Based on the findings, there are characters and settings in tehir narratives that either helped or hindered their growth and development. Settings are also important factors in their narratives. Through the findings and analysis this study can conclude three (3) things: (1) narrative is significant; (2) Communication is vital; and (3) War on drugs comes in many changing forms.
Thesis (B.A. in Speech Communication)--University of the Philippines Diliman
Includes bibliographical references and appendices.